2021
DOI: 10.46549/jipvet.v11i2.107
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Sari Buah Merah (Pandanus conoideus Lam) terhadap Abnormalitas Spermatozoa Ayam Kampung

Abstract: Antioxidants are substances that can prevent the occurrence of free radical antioxidation reactions in lipid oxidation.  Red fruit (Pandanus conoideus Lam) is one of the plants endemic to Papua which contain high antioxidant. The aim of this research was to determine the abnormality spermatozoa of ayam Kampung which were received red fruit extract treatment.  Eight cokcs were divided into 4 treatments, each treatment was repeated 5 times. The treatment consisted of control (P0) without extract, P1 with 0.5 mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The results of this study indicated that the range of lymphocyte counts for male turkeys during the growth period ranged from 55.50% -60.75%, where the average number was in an unhealthy condition. The normal lymphocyte count in male turkeys during the growth period is around 50.6% (Tethool et al, 2009).…”
Section: Lymphocytesmentioning
confidence: 99%
“…The results of this study indicated that the range of lymphocyte counts for male turkeys during the growth period ranged from 55.50% -60.75%, where the average number was in an unhealthy condition. The normal lymphocyte count in male turkeys during the growth period is around 50.6% (Tethool et al, 2009).…”
Section: Lymphocytesmentioning
confidence: 99%
“…Finally, the structure will be logical, concise, and grammatically accurate. Red fruit juice boasts α-tocopherol, βcarotene, oleic acid, linoleic acid, linolenic acid, vitamin C, calcium, phosphorus, and iron (Tethool et al, 2021;Nurcholisa et al, 2021). Tabatabaei et al (2011) suggest that antioxidants, including tocopherol, β-carotene, and ascorbic acid, can protect spermatozoa cells from cellular morphological damage, which can lead to abnormalities in these cells by preventing the negative effects of free radicals.…”
mentioning
confidence: 99%